Analysis Of A Linear Design For A Sports Utility Vehicle In Slalom Manoeuvres - Omar, Mohd Firdaus; Ghazali, Rozaimi; Aripin, Muhamad Khairi; Soon, Chong Chee; Saadon, Intan Mastura (International Journal of Mechanical Engineering and Robotics Research, 2019)
In the past two decades, automotive manufacturing has witnessed some advancements, especially for vehicle handling and active safety systems (ASSs). Progressively, more controllers have been designed to deal with linear and non-linear systems. However, studies and research on integral terms in linear quadratic regulators are scarce. In this paper, linear controllers, including the proportional integral derivative (PID) and linear quadratic integral (LQI) using direct yaw control (DYC), have been designed and compared. With the interference of external disturbances and variation of the friction coefficient, the result indicates that the LQI controller produces a significant improvement in the vehicle slalom manoeuvre system compared to the PID controller.